An assessment of economic viability of jatropha plantation in North East India. Issue 4 (4th November 2019) - Goswami, Kishor; Choudhury, Hari K.; Hazarika, Atanu; Tripathi, Rohit
Abstract : Purpose: This paper aims to analyze the economic viability of jatropha plantation in North East India. Design/methodology/approach: Economic viability is measured through the net present value and the benefit–cost ratio (BCR) at four different production standards along with four different prices of jatropha seed. Findings: At a very low price and small production, jatropha plantation is economically not feasible. However, when the price of seed increases from INR 5 to 8, BCRs become greater than 1, provided that the discount rate is less than equal to 8 per cent. The minimum threshold of BCR indicates that the threshold of 1.5 BCR at a production level of 1.5 tons/ha can be achieved with a combination of seed price of INR 10 per kg and a discount rate of 1 to 3 per cent. Thus, jatropha cultivation is economically viable but not highly profitable. Research limitations/implications: Present study analyzes the economic viability of jatropha plantation from purely financial point of view. Social cost and benefit of energy crop plantation is not included in the study. This suggests to adopt social cost–benefit analysis to evaluate the overall feasibility of plantation crops in future studies. Originality/value: This paper contributes to the academic literature of economic viability of energy plantation crops. Economic viability of jatropha plantation is shown in different cost and revenue conditions with statistical evidences.